Foresight in sight. How to improve urban resilience with collaboration among public authorities? - Molarius, Riitta; Wessberg, Nina; Keränen, Jaana; Murtonen, Mervi (Springer, 2018)
Creating a resilient built environment for citizens is one of the main issues public authorities face when planning urban areas, such as new residential areas, suburbs, shopping centres, or traffic stations. Today, in particular, the safety and security of the built environment focuses on city planning. New technologies, including digitalisation, as well as citizens with differing feelings about and experiences of safety and security challenge city planners, and this requires attention. Utilising foresight methods, such as the participatory scenario-building method, is one way to adapt to future changes in urban settlements and help decision-makers in creating a better tomorrow for citizens. This paper presents one foresight method, termed scenario-building process, as a tool for city planners to create a safer and more secure built environment for citizens with different needs and backgrounds. The paper discusses how to use participatory scenario building together with city authorities and other stakeholders for planning urban areas. By presenting a case study from Finland, where the method was used to develop the area around a railway junction station, the paper brings out four scenarios developed to visualise possible future paths of the studied railway station area. The case study was part of the HARMONISE - A Holistic Approach to Resilience and Systematic Actions to Make Large-Scale Built Infrastructure Secure - project that was funded by the European Union within the Framework Programme 7.
Keywords: Stadtplanung; Städtische Infrastruktur; Infrastrukturplanung; Risikoanalyse; Risikovorsorge; Szenario-Methode; Partizipation; Bewohnerbeteiligung